2020
DOI: 10.5397/cise.2020.00031
|View full text |Cite
|
Sign up to set email alerts
|

Clinical results of conservative management in patients with full-thickness rotator cuff tear: a meta-analysis

Abstract: Background: Several systematic reviews have reported on the conservative treatment of full-thickness rotator cuff tears; however, clinical results of this treatment still remain determined. Methods: PubMed, Cochrane Library, PEDro, and CINAHL databases were systematically searched for randomized clinical trials and observational studies. Two independent researchers reviewed a total of 2,981 articles, 28 of which met the criteria for inclusion in the study. Clinical outcome measures included Constant score, vis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 33 publications
0
8
0
Order By: Relevance
“…Rotator-cuff tears are the most frequent shoulder pathologies that cause pain and functional impairment 9 , 10 . Numerous authors have reported surgical methods and clinical outcomes of supraspinatus tendon repair 7 , 11 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Rotator-cuff tears are the most frequent shoulder pathologies that cause pain and functional impairment 9 , 10 . Numerous authors have reported surgical methods and clinical outcomes of supraspinatus tendon repair 7 , 11 13 .…”
Section: Discussionmentioning
confidence: 99%
“…Delaminated RCTs are mainly found in degenerative tears. 4,9,23 The reported incidence of delaminated RCTs is between 32% and 88%. 10 Boileau et al 2 reported delaminated tears in 32% of patients after arthroscopic repair of medium or large chronic full-thickness RCTs.…”
mentioning
confidence: 99%
“…Rotator cuff tear is a common disorder that causes severe pain and disability. 13,14,29 The goal of rotator cuff repair is to fix the ruptured tendon to the footprint, maintain mechanical stability during loading, and achieve secure biological tendon-to-bone healing. 26 Although surgical techniques and instrumentation have developed considerably in the past years, the failure rate of rotator cuff healing after repair is still high and an unsolved problem.…”
mentioning
confidence: 99%